Australia must fight Internet crime and support its victims - Roberts, Lynne (Greenhaven Press, 2010)
In this viewpoint, Lynne Roberts provides examples of how Australia is fighting Internet crime and suggests that even more programs are needed to fight an ever-increasing amount of online predators. Roberts especially focuses on the individuals who are targets of Internet crime, who are rarely given the necessary help to deal with their victimization. Additionally; Roberts suggests a host of measures, from Internet filters for children to educational training, which can make Web surfers more aware of the pitfalls of Internet use. Finally, Roberts suggests that more studies are needed to deal adequately with this burgeoning type of victimization.